CHARAKTER PRAWNY WSPÓŁUCZESTNICTWA PROCESOWEGO POSIADACZA POJAZDU MECHANICZNEGO I UBEZPIECZYCIELA W PROCESIE ODSZKODOWAWCZYM Z TYTUŁU OBOWIĄZKOWEGO UBEZPIECZENIA ODPOWIEDZIALNOŚCI CYWILNEJ - Mucha, Joanna (Wydział Prawa i Administracji UAM, 2009)
The purpose of the paper is to establish the legal nature of the relationship between the insurer and the insured party as defendants in an action for damages instigated by the injured party. The specificity of that relationship is considered in the light of substantive law from the point of view of limited solidarity and the principle of indiividual liability of the defendants These considerations take into account the characteristics of different kinds of joint participation in civil law proceedings. The analysis of the above has led to a conclusion that joint participation in a dispute between the insurer and the insured is a substantive joint participation based on a common obligation with a partly different factual and legal basis, and in consequence the sentance can be different for either of the defendents.
LEGAL NATURE OF JOINT PARTICIPATION OF A MOTOR VEHICLE OWNER AND AN INSURER IN AN ACTION FOR DAMAGES ARISING FROM THE MANDATORY CIVIL LIABILITY INSURANCE